To use or not to use, that is the question. Analysis of the determining factors for using NFC Mobile Payment Systems in Public Transportation. - Liébana Cabanillas, Francisco; Molinillo-Jiménez, Sebastián; Ruiz Montañez, Miguel (Elsevier, 2018)
There is growing interest in our society in making payments using mobile phones as an alternative to using cash, checks or credit cards. The objective of this study is to analyze the status of Near Field Communication (NFC) mobile payment systems in public transportation, as well as the factors that affect users' intentions to continue using said systems. To meet this objective, a personal survey was conducted on a sample of 180 users with experience using this type of system. A comprehensive review of the scientific literature justifies the development of a behavioral model that explains the continuance intention of NFC mobile payments through a structural equation model. The results show that satisfaction, service quality, effort expectancy, and perceived risk are determining factors of the continuance intention to use this technology. Finally, the managerial conclusions and implications offer the companies that manage these public services new business opportunities based on user behaviors.
Política de acceso abierto tomada de: https://v2.sherpa.ac.uk/id/publication/16965 (submitted version)
Keywords: Transporte - Innovaciones tecnológicas; Mobile payment; NFC; Structural equation model; Continuance intention